Manifesta young women, feminism, and the future - Baumgardner, Jennifer 1970-; Richards, Amy 1970- (Picador, 2020)
Today, people of all genders strive to uphold the goals of feminism and proudly embrace the term, but the movement itself is often beset with confusion and questions. Does personal empowerment happen at the expense of politics? Is feminism for the few--or does it speak to the many as they bump up against daily injustices? What does it mean to say "the future is female"? In 2000, Jennifer Baumgardner and Amy Richards's Manifesta set out to chronicle the feminism of their generation. They brilliantly revealed the snags in various hubs of the movement--from antipathy to the term itself to the hyped hatred of feminism's imperfect spokespeople--and showed that these snags had not imperiled the feminist cause. The book went on to inspire a new generation of readers and has become a classic of contemporary feminist literature. In the decades since Manifesta was published, the world has changed in ways both promising and terrifying. This twentieth anniversary edition of Manifesta features an updated bibliography, timeline, and resources, as well as a new introduction by the authors. Expertly unpacking both early women's history and the Third Wave feminism that seeded the active righteous intersectionality we see today, Manifesta remains an urgent and necessary tool to make sense of our past, present, and future
Keywords: Junge Frau; Aktivismus; Feminismus; USA; Feminism / United States; Young women / United States / Attitudes; Feminism; Young women / Attitudes; United States